PENGEMBANGAN E-MODUL PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI MENGGUNAKAN APLIKASI CANVA DAN WORDWALL MATERI FAKTOR- FAKTOR KEMAJUAN PERADABAN ISLAM DI DUNIA UNTUK SISWA KELAS XII SMA BSS MALANG - Lathifa Budiaty Mawaddah; Lia Nur Atiqoh Bela Dina; Atika Zuhrotus Sufiyana (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
Learning modules as one of the important aspects in supporting the achievement of learning objectives need to be made as attractive and effective as possible. One of them is by utilizing the increasingly diverse types of information technology. One form of using technology in education is what SMA BSS Malang does by changing the print module to an e-module during the learning process. However, the e-module made is less attractive because it only displays text and images without any video or animation, so it is necessary to develop the e-module. The development of this emodule was carried out by combining two applications, namely Canva and Wordwall and was developed using the ADDIE model consisting of Analysis, Design, Development, Implementation, and Evaluation. From the development that has been carried out, it shows that the product developed is effective because it is able to significantly increase the average student learning outcomes before using the emodule before using the e-module and getting a response that is in accordance with the results from material experts 87.31%, design and engineering experts. languages 84.65%, and expert practitioners 95.5%.